Gestational Diabetes Mellitus in Far North Queensland, Australia, 2004 to 2010: midwives' perinatal data most accurate source - Catherine Chamberlain; Bronwyn Fredericks; Anna McLean; Bronwyn Davis; Sandra Eades; Kirsten Stewart; Chris M. Reid (Elsevier, 2013)
Abstract Objectives: This study examines the accuracy of Gestational Diabetes Mellitus (GDM) case‐ascertainment in routinely collected data. Methods: Retrospective cohort study analysed routinely collected data from all births at Cairns Base Hospital, Australia, from 1 January 2004 to 31 December 2010 in the Cairns Base Hospital Clinical Coding system (CBHCC) and the Queensland Perinatal Data Collection (QPDC). GDM case ascertainment in the National Diabetes Services Scheme (NDSS) and Cairns Diabetes Centre (CDC) data were compared. Results: From 2004 to 2010, the specificity of GDM case‐ascertainment in the QPDC was 99%. In 2010, only 2 of 225 additional cases were identified from the CDC and CBHCC, suggesting QPDC sensitivity is also over 99%. In comparison, the sensitivity of the CBHCC data was 80% during 2004-2010. The sensitivity of CDC data was 74% in 2010. During 2010, 223 births were coded as GDM in the QPDC, and the NDSS registered 247 women with GDM from the same postcodes, suggesting reasonable uptake on the NDSS register. However, the proportion of Aboriginal and Torres Strait Islander women was lower than expected. Conclusion: The accuracy of GDM case‐ascertainment in the QPDC appears high, with lower accuracy in routinely collected hospital and local health service data. This limits capacity of local data for planning and evaluation, and developing structured systems to improve post‐pregnancy care, and may underestimate resources required. Implications: Data linkage should be considered to improve accuracy of routinely collected local health service data. The accuracy of the NDSS for Aboriginal and Torres Strait Islander women requires further evaluation.